Design Optimization of A Conventional Rocket Nozzle Using Coupled Thermo-Structural Analysis - Saputra, M. Dito; Andria, Novi (Indonesian Journal of Aerospace, 2021)
Thrust in a rocket is gained by expelling the combustion gas through a nozzle. Â This rocket nozzle is a vital component during the conversion of chemical energy into kinetic energy. Consequently, it is exposed to extreme temperature and pressure resulted from gas combustion. Therefore to ensure a successful rocket operation, the nozzle must be able to maintain structural integrity when exposed to such environment. On the other hand, its structural weight must be kept minimum to reduce the overall weight of the rocket. Due to these circumstances, the nozzle design phase is very important since the nozzle significantly affects the whole rocket performance. LAPAN is currently developing some solid propellant based rocket. Each rocketâ€™s nozzle is still designed using conventional configuration, consisting of a metal case and graphite insert. The nozzle relies on a thick structure geometry to maintain structural integrity. This approach induces a heavy-weight nozzle that burdens the rocket performance. This paper is attempted to optimize LAPANâ€™s conventional solid rocket nozzle design. A series of procedures are proposed to generate a lighter nozzle design. RX-450 rocketâ€™s nozzle will be used as the studied model in this paper.Â Coupled thermo-structural analysis forms the main procedure to evaluate the proposed nozzle geometry structural integrity. The study succesfully provided an optimized nozzle geometry with sufficient strength and reduced weight.